DES modelling and control vs. problem solving methods. (20th April 2007) - Capkovic, Frantisek
Modelling and control of a kind of Discrete-Event Systems (DES) having a character of Flexible Manufacturing Systems (FMS) are examined by means of methods used in applied artificial intelligence. While assembly and/or disassembly processes are controlled by means of the problem solving methods (the so called block world and the Hanoi tower puzzle), the process of crossing vehicles inside FMS is controlled as the multi-agent system. Petri Net (PN)-based models are utilised in order to described the dynamic behaviour of the systems. The control strategy based on Reachability Graphs (RGs) is proposed and illustrated. Feasible state trajectories in the space of feasible states are found. The set of discrete events corresponding to particular segments of the trajectories represents the result of control synthesis.